Epizootological features of canine babesiosis in the Volgograd Region - S. A. Akimova; A. A. Ryadnov; S. A. Fomenko (Российский паразитологический журнал, 2025)
The purpose of the research is to study epizootological features of canine babesiosis in the Volgograd Region.Materials and methods. The epizootological situation on canine babesiosis in the Volgograd Region was studied in 2019 2024. Babesiosis was diagnosed based on anamnestic data, clinical study results, and laboratory diagnostics. Blood for smears was taken from the tail vessels in puppies, and ear blood vessels in adult dogs. Smears were fixed with methylene alcohol and stained by the Romanowsky-Giemsa staining, and statistical materials from Volgograd and Volgograd Region veterinary clinics were analyzed.Results and discussion. Results of clinical and laboratory examinations of dogs in the Volgograd Region show that babesiosis annually occur as two outbreaks from April to May; a less pronounced outbreak is from October to November. The infection prevalence was 3.22–4.04% in the study of dogs’ blood smears. The current situation was analyzed for canine babesiosis in the Volgograd Region over the past 6 years, from 2019 to 2024. This disease has a major effect on dog breeding, since it has taken an atypical form in recent years and can even occur in the winter months. The largest number of patients with babesiosis was in the age group of 1 to 4 years (41.0%); slightly less, in the group over 4 years (31.9%); and the smallest number, under 1 year (27.1%).